Scalability of lineament and fracture networks within the crystalline Wiborg Rapakivi Batholith, SE Finland - Ovaskainen, Nikolas (My University, 2020)
Multiscale lineament and fracture extraction conducted within the Wiborg Rapakivi Batholith offers insights both into the brittle bedrock structures of the batholith and to the scale-dependence of lineament and fracture analysis results. Multiscale fracture studies from crystalline rocks are sparse even though brittle structures in the crystalline bedrock significantly affect the flow models of fluids, hydrothermal heat and hydrocarbons, and are the main factor controlling the permeability in crystalline rocks. The main goal of this study is to assess the scalability of lineament and fracture networks through statistic characterization of lineament and fracture datasets extracted from four scales of observation using geometric and topological parameters, and by studying the subsequent correlations between the dataset characterizations. The parameters are acquired from both the individual lineaments and fractures and from their respective networks. Brittle bedrock structures were extracted manually using two principle methods: lineament traces were digitized from Light Detection And Ranging (LiDAR) digital elevation models and fracture traces were digitized from drone-based orthophotography of bedrock outcrops. Both extractions result in two-dimensional datasets and, consequently, all characterizations of these datasets along with the scalability analysis results are limited to two dimensions. The crystalline Wiborg Rapakivi Batholith is structurally isotropic and lithologically sufficiently homogeneous so that the effect of both precursor fabrics and lithological variations can be ignored when considering the genesis and emplacement of brittle bedrock structures in the batholith. Scalability analyses conducted within this investigation revealed that the results of lineament and fracture network extractions are always dependent on the scale of observation. Even dimensionless parameters of networks, such as connectivity, were found to follow a scale-dependent trend: The apparent connectivity of a lineament or fracture network decreases as the scale of observation increases. The characterizations of the datasets were used for the interpretation of Wiborg Rapakivi Batholith fracture patterns and paleostresses, which could be compared to Olkiluoto site studies of paleostresses in southern Finland.

Viipurin rapakivibatoliitin alueella useassa mittakaavassa tehty lineamenttien ja rakojen kartoitus antaa tietoa sekä batoliitin hauraista kallioperän rakenteista että lineamentti- ja rakokartoituksen tulosten skaalariippuvuudesta. Useassa mittakaavassa tehtävät rakotutkimukset kiteisistä kivistä ovat harvinaisia, vaikka kiteisen kallioperän hauraat rakenteet vaikuttavat vahvasti nesteiden, kaasujen, hydrotermisen lämmön ja hiilivetyjen virtausmalleihin ja ne ovat kiteisen kallioperän permeabiliteetin tärkein kontrolloija. Tämän tutkimuksen tärkein tavoite on lineamentti- ja rakoverkkojen skaalautuvuuden tutkiminen. Tutkiminen tapahtuu ensin karakterisoimalla tilastollisesti lineamentti- ja rakoaineistoja neljästä eri mittakaavasta käyttäen geometrisiä ja topologisia parametrejä, ja sitten tutkimalla aineistojen karakterisointien välisiä korrelaatioita. Parametrit ovat sekä yksittäisten lineamenttien ja rakojen että lineamentti- ja rakoverkkojen parametrejä. Kallioperän hauraat rakenteet kartoitettiin kahdella eri metodilla: lineamenttiviivat digitoitiin laserkeilauskorkeusmalleista (LiDAR DEMs) ja rakoviivat digitoitiin lennokilla otetuista kalliopaljastumien ortomosaiikkikuvista. Molempien kartoitusten tuloksena oli kaksiulotteisia aineistoja, ja tämän takia myös kaikki aineistojen karakterisoinnit ja skaalautuvuusanalyysien tulokset ovat kaksiulotteisia. Kiteinen Viipurin rapakivibatoliitti on rakenteellisesti isotrooppinen ja litologisesti riittävän homogeeninen, jotta sekä edeltävät rakenteet että litologiset vaihtelut voidaan jättää huomioimatta, kun tutkimuksen kohteena on batoliitin hauraiden rakenteiden syntyminen. Tämän tutkimuksen puitteissa tehdyt skaalautuvuusanalyysit osoittivat, että lineamentti- ja rakoverkkokartoitusten tulokset ovat aina riippuvaisia kartoituksen mittakaavasta. Jopa yksiköttömät verkkojen parametrit, kuten verkottuneisuus, seurasi skaalariippuvaista trendiä: Näennäinen lineamentti- tai rakoverkon verkottuneisuus pienenee, kun mittakaava suurenee. Lineamentti- ja rakoaineistojen karakterisointeja käytettiin Viipurin rapakivibatoliitin rakojen muodostamien kuvioiden ja paleostressien tulkintaan. Paleostressitulkintoja voi verrata Olkiluodossa tehtyihin tutkimuksiin paleostresseistä eteläisessä Suomessa.
Keywords: crystalline bedrock,multiscale,fractures,fracture networks,lineaments,lineament networks,structural geology,topology